NATURAL DURABILITY OF Cupressus lusitanica, Cryptomeria japonica AND Pinus taeda WOODS IN FIELD TRIAL - Vivian, Magnos Alan; Nunes, Gláucia Cota; Dobner Jr., Mário; Modes, Karina Soares; Grosskopf, Évelyn Janaina; Belini, Ugo Leandro (Floresta, 2020)
The purpose of this study was to evaluate the natural durability of Cupressus lusitanica, Cryptomeria japonica and Pinus taeda woods subjected to a rotting field trial, through mass loss and deterioration index. The trial was conducted in an open field in the city of Curitibanos, State of Santa Catarina, Brazil, for a 24-month period, with evaluations carried out every 6 months. For developing the study, we used the woods of Cupressus lusitanica (16 years), Cryptomeria japonica (16 years) and Pinus taeda (juvenile=15 years and mature wood>30 years) species, from which test specimens were made with the dimensions of 2.5 x 5.0 x 50.0 cm in thickness, width and length, respectively, following the standards suggested by IUFRO. After 24 months of exposure to the rotting field the woods of C. japonica and C. lusitanica species showed a deterioration index that reflected an evident but moderate attack of fungi and termites, while the woods of P. taeda (juvenile) and P. taeda (mature) showed deterioration index that reflected an intense rotting and intense attack of termites. Regarding the mass loss the woods of C. japonica and C. lusitanica were classified as highly resistant, while P. taeda (juvenile) was considered resistant and P. taeda (mature) was considered moderately resistant. In general, the woods of C. lusitanica and C. japonica showed greater natural durability when used in contact with the soil.